High-cycle fatigue and fracture behavior of double-side friction stir welded 6082Al ultra-thick plates. (1st March 2020) - Yang, C.; Wang, B.B.; Yu, B.H.; Wu, L.H.; Xue, P.; Zhang, X.M.; He, G.Z.; Ni, D.R.; Xiao, B.L.; Wang, K.S.; Ma, Z.Y.
Highlights: 6082Al ultra-thick plates were successfully welded by friction stir welding (FSW). High cycle fatigue behavior was first studied on FSW joint of ultra-thick Al plate. Abnormal fracture in nugget zone was observed for upper layered specimen. Tensile residual stress together with cyclic stress resulted in abnormal fracture. Abstract: For welded structures of precipitation-strengthened aluminum alloys, achieving sound joint with good fatigue property is not an easy task, especially for thick plates. In the present work, ultra-thick 6082Al-T4 alloy plates with 80 mm in thickness were double-side friction stir welded and heat-treated. The high cycle fatigue (HCF) property and fracture behavior of the joint were investigated using trisection specimens in thickness, and the key factors that affect the fracture behavior were addressed. High quality joint was achieved with the three-layered specimens fractured along the lowest hardness zone (LHZ) in the static tensile testing. Further, the fatigue life curves exhibited almost the same distribution tendency, and the same fatigue limit (110 MPa) and fatigue ratio (0.49) were achieved in the three-layered specimens. During fatigue testing, the middle and lower layers fractured along the LHZ, which was similar to those during the static tensile tests, while abnormal fracture occurred in the nugget zone (NZ) of the upper specimen. Further examination revealed that the residual stress in the NZ of the upper layer was tensile stress (+9 MPa) whereas it was compressive stress in the lower layer (–31 MPa). The tensile residual stress together with the external loaded cyclic tensile stress resulted in more serious fatigue damage in the upper layer and led to the abnormal fracture in the NZ.